The Effect of Return on Asset, Debt to Equity Ratio, and Current Ratio Towards The Value of Companies Implementing ESG on The Indonesia Stock Exchange in 2023: ESG Risk Rating as a Moderating Variable - Nur, Alny Miladia; Utami, Yuni; Hapsari, Ira Maya (Baca Dulu Publisher, 2024)
This study aims to determine and analyze the effect of Return On Asset, Debt To Equity Ratio, and Current Ratio on Firm value with ESG Risk Rating as a Moderating Variable in Companies Implementing ESG on the Indonesia Stock Exchange in 2023. This type of research is quantitative. The data used is secondary data. The sample data obtained were 79 research data from 79 companies in 2023. Data analysis techniques using descriptive statistical tests, classical assumption tests, multiple linear regression analysis tests, t-statistic tests, determination coefficient tests (R2), and subgroup moderation tests. Hypothesis testing is carried out using the SPSS 25 program. The results of the study indicate that return on assets has no effect on firm value, debt to equity ratio has a negative effect on firm value, current ratio has a negative effect on firm value, ESG risk rating cannot moderate the effect of return on assets on firm value, ESG risk rating cannot moderate the effect of debt to equity ratio on firm value, ESG risk rating cannot moderate the effect of current ratio on firm value.